5^-1 = 1/5
so, -(5)^-2 = -1/5
except for zero, anything to the zero power is 1.
Think about it. x^3/x^3 = x^(3-3) = x^0
whatever number you choose, raising it (or any power of it) to the zero power just gives 1.
Negative powers switch numbers from the top to the bottom (or vice-versa) in fractions.
1/(p^-6) = 1/(1/p^6) = p^6
so, -1/p^-6 = -p^6
(3^2 y^-2)/(2^3 x^-3) = (3^2 x^3)/(2^3 y^2)
i need help with these questions
1. -(5)^-1
A.-1/5
B.-5
C.5
D.1/5
2.(-4.7)^0
A.1* i think this one
B.-1
C.0
D.-4.7
3.-1/p^-6
A.-6/p
B.-6p
C.-p^6
D.p^6
if anyone knows the rest please help.
2 answers
1) I suppose you mean - (1/5) for number 1, which is A, of course.
2) There is a exponential rule that states that any base to a power 0 will give the result of 1.
3) -1 / (p)^-6 ==> -1/ (1/p^6) ==> -p^6.
2) There is a exponential rule that states that any base to a power 0 will give the result of 1.
3) -1 / (p)^-6 ==> -1/ (1/p^6) ==> -p^6.